HLA antibodies and their value during renal transplantation - M. Sh. Khubutia; N. V. Borovkova; R. V. Storozhev; N. V. Doronina; M. V. Storozheva; A. S. Pertsev; A. V. Pinchuk (Трансплантология (Москва))
Objective: to evaluate the effects of pre-existing HLA antibodies on the posttransplantation period and to study changes in the generation of donor-specific antibodies in recipients after allogeneic cadaveric kidney transplantation.Materials and methods. One hundred and ten serum samples from patients on the kidney transplantation waiting list (WL) were tested for pre-existing HLA antibodies. To evaluate the effect of preantibodies, the investigators examined 55 patients (32 males and 23 females, whose age was 28 to 63 years) who had undergone kidney transplantation at the N.V. Sklifosovsky Research Institute of Emergency Care in October 2009 to September 2010. In the second part of the investigation, HLA antibody levels were monitored in the posttransplantation period. A total of 27 patients (15 males and 12 females aged 26 to 61 years) were examined after kidney transplantations made at the N.V. Sklifosovsky Research Institute of Emergency Care in March to September 2010.Results and discussion. Since November 2009, the serum level of pre-existing HLA antibodies had been measured in all the patients registered on the kidney transplantation WL at the N.V. Sklifosovsky Research Institute of Emergency Care. One hundred and ten patients have been examined today; of them 69 males and 41 females are waiting for kidney transplantation.Conclusion. The level of pre-existing HLA antibodies must be estimated in the recipients to be prepared for kidney transplantation since this makes it possible to identify in practice a group of patients requiring a more thorough selection of donor organs and preoperative preparation that involves the methods of extracorporeal blood correction and medical therapy.